The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1128/mcb.12.6.2720
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements for enhancement of T-cell responsiveness by the lymphocyte-specific tyrosine protein kinase p56lck.

Abstract: To understand the mechanism(s) by which p56kk participates in T-cell receptor (TCR) signalling, we have examined the effects of mutations in known regulatory domains of p56kk on the ability of F505 p561k to enhance the responsiveness of an antigen-specific murine T-cell hybridoma. A mutation of the amino-terminal site of myristylation (glycine 2), which prevents stable association of p56kk with the plasma membrane, completely abolished the ability of F505 p56kk to enhance TCR-induced tyrosine protein phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 47 publications
6
47
0
Order By: Relevance
“…Ag-independent T cell SFK activation by DCs has been observed previously (36), but the functional consequences for T cell activation remained unclear. In this study, we show that Ag-independent DC-mediated SFK activation does not result in full TCR activation, as T cells fail to undergo substantial phosphorylation of CD3 or TCR down-modulation (37) (Fig. 2A).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Ag-independent T cell SFK activation by DCs has been observed previously (36), but the functional consequences for T cell activation remained unclear. In this study, we show that Ag-independent DC-mediated SFK activation does not result in full TCR activation, as T cells fail to undergo substantial phosphorylation of CD3 or TCR down-modulation (37) (Fig. 2A).…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, an up-regulated serial TCR triggering capacity of DCs is equally unlikely. This reasoning is evidenced by the fact that Lck activation results in enhanced TCR signaling in response to TCR agonists that are fully incapable of serial triggering (37,38). Thus, it follows that up-regulation of the serial TCR triggering rate is unlikely the mechanistic reason for superior T cell stimulation by SFK-mediated TCR licensing.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of Tyr-394 to phenylalanine not only decreases Lck activity in unstimulated cells, but also prevents activation of Lck by oxidative stress. In addition, Lck that has been genetically activated by mutation of Tyr-505 to phenylalanine loses its transforming ability when Tyr-394 is also mutated to phenylalanine (21,40). We previously showed that the extent of Tyr-505 phosphorylation in Lck from H 2 O 2 -stimulated cells was at least as great as that of Tyr-394.…”
Section: Discussionmentioning
confidence: 99%
“…The results using A2 and A6 Lck mutants in this study indicated a preferential role of myristoylation for membrane localization of Lck. Earlier study demonstrated the importance of myristoylation at glysine 2 of Lck in T cell function (27). Recently, Kabouridis et al (28) reported that palmitoylation of Lck at cysteine 3 and 5 is essential for its signaling function in T cells.…”
Section: Discussionmentioning
confidence: 99%